HUBUNGAN ANTARA KESEPIAN DAN MOTIF PERSAHABATAN DENGAN KOMUNIKASI ON LINE PADA REMAJA AKHIR - Agoes Dariyo (Universitas Katolik Soegijapranata, 2016)
Aim of this research is to know correlation between loneliness, friendship motive; and on line communication on adolescence. We use questionnaires of loneliness, friendship motive and on line communication, to collect the data. The sum of subjects in this research are 286 adolescences ( 86 men and 200 women ). We analysis data with correlation technique. Found, there are negative correlation between loneliness and friendship motive (r = -. 439, p = .000 < .01), there are negative correlation between loneliness and on line communication ( r = -.154, p = .009 < .05), there are correlation between motive friendship and on line communication (r = .358, p = .000 < .01).